Fibroblast Growth Factor Receptor (FGFR) Inhibitors in Urothelial Cancer. (15th September 2020) - Garje, Rohan; An, Josiah; Obeidat, Mohammad; Kumar, Kranthi; Yasin, Hesham A.; Zakharia, Yousef
Abstract: : Dysregulated fibroblast growth factor receptor (FGFR) signaling is associated with several cancers, including urothelial carcinoma. Preclinical studies with FGFR inhibitors have shown significant antitumor activity, which has led to clinical evaluation of multiple FGFR inhibitors. Recently, erdafitinib was approved by the U.S. Food and Drug Administration for advanced urothelial carcinoma with FGFR gene alterations as the first molecularly targeted therapy. Additional ongoing clinical trials with other types of FGFR inhibitors have shown encouraging results. This review summarizes the oncogenic signaling of FGFR alterations, completed and ongoing clinical trials of FGFR inhibitors, and resistance patterns. Implications for Practice: Dysregulated fibroblast growth factor receptor (FGFR) signaling is associated with several cancers, including urothelial carcinoma. Preclinical studies with FGFR inhibitors have shown significant antitumor activity, which has led to clinical evaluation of multiple FGFR inhibitors. Most recently, erdafitinib was approved by the U.S. Food and Drug Administration for advanced urothelial carcinoma with FGFR gene alterations as the first molecularly targeted therapy. Additional ongoing clinical trials with other types of FGFR inhibitors have shown encouraging results. This review summarizes the oncogenic signaling of FGFR alterations, completed and ongoing clinical trials of FGFR inhibitors, and resistance patterns. Abstract : Focusing on urothelial malignancies, this review summarizes the oncogenic signaling of FGFR alterations, clinical trials of FGFR inhibitors, and resistance patterns.